2008
DOI: 10.1002/pc.20451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crosslinking density on structure and properties of interpenetrating polymer networks from polyurethane and nitroguar gum

Abstract: Semi-interpenetrating polymer networks (semi-IPNs) of castor oil-based polyurethane prepolymer and nitroguar gum (NGG) with different crosslinking density of the PU network, coded as UNG films, were prepared through varying the trimethanol propane (TMP)/1,4butanediol (BDO) molar ratios in the chain extender mixture. The effects of crosslinking density on the structure and properties of the UNG films was investigated by attenuated total reflection Fourier transform infrared spectroscopy, differential scanning c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…One of the most frequently used renewable raw materials are cashew nut shell liquid for getting polyols . Vegetable oil has also been blended to prepared polyols as a starting material for Pus . Petrovic et al have reported the preparation of rigid type PUs from soybean oil .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most frequently used renewable raw materials are cashew nut shell liquid for getting polyols . Vegetable oil has also been blended to prepared polyols as a starting material for Pus . Petrovic et al have reported the preparation of rigid type PUs from soybean oil .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Vegetable oil has also been blended to prepared polyols as a starting material for Pus. 14,15 Petrovic et al have reported the preparation of rigid type PUs from soybean oil. 16 There are several reports available on the PUs based on soybean oil, castor oil, nahar seed oil, rape seed oil, and plam oil.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, environment‐friendly materials from renewable raw materials such as cellulose, starch, polysaccharides, protein, plant oil, and so forth, have been used to obtain an easily degradable and low toxicity polymer matrix. This can be achieved by the synthesis of synthetic polymers from natural resources or by mixtures of synthetic polymers with natural polymers 2, 14, 15. One of the most frequently used renewable raw materials for polymer applications are plant oils.…”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform infrared spectroscopy can speculate the composition of PU samples according to the specific absorption frequency and thus give qualitative results . On contrast, nuclear magnetic resonance can help to give quantitative results because the molar ratio of hydric groups is available by referring to different hydrogen atom’ chemical shifts in 1 H‐nuclear magnetic resonance spectra . Besides, apart from TGA analysis carrying out in this study, differential scanning calorimetry, and dynamic thermomechanical analysis are two kinds of common thermal analysis.…”
Section: Resultsmentioning
confidence: 99%